Passing for Spain : Cervantes and the fictions of identity - Fuchs, Barbara, 1970- (Hispanisms., 2003)
"Passing for Spain charts the intersections of identity, nation, and literary representation in early modern Spain. Barbara Fuchs analyzes the trope of passing in Don Quijote and other works by Cervantes, linking the use of disguise to the broader historical and social context of Counter-Reformation Spain and the religious and political dynamics of the Mediterranean Basin." "In five engaging chapters, Fuchs examines what passes in Cervantes's fiction: gender and race in Don Quijote and "Las dos doncellas"; religion in "El amante liberal" and La gran sultana; national identity in the Persiles and "La española inglesa." She argues that Cervantes represents cross-cultural impersonation - or characters who pass for another gender, nationality, or religion - as a challenge to the state's attempts to assign identities and categories to proper Spanish subjects."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved